Achieving additive-free organic solar cells by modulating the side-chain length of non-fullerene small molecule acceptors. (November 2021) - Xin, Yue; Liang, Jionghong; Zhong, Yu; Liang, Tianlong; Zhang, Chi; He, Xin
Abstract: After several years of development, the power conversion efficiencies (PCEs) of organic solar cells (OSCs) based on non-fullerene small molecule acceptors (NF-SMAs) can be more than 17 %. However, the addition of solvent additives, which could lead to complicated device processing and poor repeatability, is often the premise of obtaining high PCEs. Here, the impact of the side-chain length and solvent additives on device performance were investigated by synthesizing three NF-SMAs based on dithieno[3, 2-b:2′, 3′-d]pyrrole with 2-ethylhexyl (SNC2C4–F ), 2-butyloctyl (SNC4C6–F ) and 2-hexyldecyl (SNC6C8–F ) attached to the N atom. The results showed that the acceptors with longer alkyl side chains were less likely to aggregate in the as-cast active layers. Consequently, the device based on SNC4C6–F, exhibiting the most suitable phase separation and morphology, demonstrated an ideal PCE of 10.71 %, which was higher than that of the other two systems. However, after being treated with 1-chloronaphthalene (1-CN), the morphologies of the active layers based on SNC2C4–F and SNC6C8–F were improved, and the corresponding devices also displayed increased PCEs (>10 %). On the other hand, the SNC4C6–F -based active layer treated with 1-CN showed a deteriorated morphology, leading to a reduced PCE. The findings of this work suggested that adjusting the length of alkyl side chains could achieve the optimal PCEs without additional additive treatment. Graphical abstract: Image 1 Highlights: Three new acceptors with different side-chian length were designed and synthesized. The change in the side-chain length could significantly affect the morphology of active layers and device performance. Adjusting the length of alkyl side-chains could achieve the optimal PCEs without additional additive treatment.